Decoding TBCK: from bioinformatic insights of domain architecture to disease implications - Cagwin, Emma M.; Padgett, Caitlin M.; Lin, Yvonne; Zhu, Wen (Frontiers in Biophysics, 2025)
TBCK is an essential protein in neurodevelopment. Mutations in the TBCK gene are associated with TBCK Syndrome, a genetic neurological disorder characterized by global developmental delay. TBCK is an enigmatic multidomain protein that contains a pseudokinase domain, a TBC (Tre2-Bub2-Cdc16) domain, and a rhodanese-like domain. Emerging evidence increasingly links TBCK to multiple cellular processes, including mTOR signaling, autophagy, lysosomal function, and mitochondrial maintenance. This review consolidates recent advances in our understanding of TBCK, emphasizing comparative sequence analysis, structural modeling, and its cellular functions. Our analysis shows that both the protein kinase domain and the rhodanese-like domain likely lack catalytic activity and instead primarily function as scaffolds or regulatory domains. The TBC domain contains all the conserved residues, suggesting it may act as a GTPase-activating protein (GAP). These functional hypotheses provide a foundation for further investigations into TBCK’s physiological and pathological roles.